Systemic Lupus Erythematosus Presenting with Ischemic Proctitis and Abdominal Compartment Syndrome - Yousaf Bashir Hadi; John Lindsay; Syeda Fatima Zehra Naqvi; Hatim Al-Jaroushi (Case Reports in Gastrointestinal Medicine)
Ischemic colitis and proctitis is a rare manifestation of systemic lupus erythematosus (SLE) and results from mesenteric vasculitis. Owing to diverse blood supply and presence of multiple collaterals, rectum is the least effected site in SLE enteritis. Ischemic proctocolitis as the presenting feature of SLE is exceedingly rare, with only three cases reported in the published scientific literature. We present the first case of SLE presenting as ischemic proctitis, leading to intraperitoneal hemorrhage and abdominal compartment syndrome. A young lady presented with ischemic proctitis and a hematoma masquerading as a pelvic mass, with subsequent development of massive intraperitoneal hemorrhage, shock, and rectal perforation. The patient required urgent surgery and was initiated on high-dose steroids.